Orientia tsutsugamushi ankyrin repeat-containing protein family members are Type 1 secretion system substrates that traffic to the host cell endoplasmic reticulum - VieBrock, Lauren; Evans, Sean M.; Beyer, Andrea R.; Larson, Charles L.; Beare, Paul A.; Ge, Hong; Singh, Smita; Rodino, Kyle G.; Heinzen, Robert A.; Richards, Allen L.; Carlyon, Jason A. (Frontiers in Cellular and Infection Microbiology, 2015)
Scrub typhus is an understudied, potentially fatal infection that threatens one billion persons in the Asia-Pacific region. How the causative obligate intracellular bacterium, Orientia tsutsugamushi, facilitates its intracellular survival and pathogenesis is poorly understood. Many intracellular bacterial pathogens utilize the Type 1 (T1SS) or Type 4 secretion system (T4SS) to translocate ankyrin repeat-containing proteins (Anks) that traffic to distinct subcellular locations and modulate host cell processes. The O. tsutsugamushi genome encodes one of the largest known bacterial Ank repertoires plus T1SS and T4SS components. Whether these potential virulence factors are expressed during infection, how the Anks are potentially secreted, and to where they localize in the host cell are not known. We determined that O. tsutsugamushi transcriptionally expresses 20 unique ank genes as well as genes for both T1SS and T4SS during infection of mammalian host cells. Examination of the Anks' C-termini revealed that the majority of them resemble T1SS substrates. Escherichia coli expressing a functional T1SS was able to secrete chimeric hemolysin proteins bearing the C-termini of 19 of 20 O. tsutsugamushi Anks in an HlyBD-dependent manner. Thus, O. tsutsugamushi Anks C-termini are T1SS-compatible. Conversely, Coxiella burnetii could not secrete heterologously expressed Anks in a T4SS-dependent manner. Analysis of the subcellular distribution patterns of 20 ectopically expressed Anks revealed that, while 6 remained cytosolic or trafficked to the nucleus, 14 localized to, and in some cases, altered the morphology of the endoplasmic reticulum. This study identifies O. tsutsugamushi Anks as T1SS substrates and indicates that many display a tropism for the host cell secretory pathway.